Effect of Spontaneous Lactic Acid Fermentation on Physico-Chemical Properties of Sweet Potato Flour - NETI YULIANA; SITI NURDJANAH; RIBUT SUGIHARTO; DEARY AMETHY (Microbiology Indonesia, 2014)
Native sweet potato flour is usually has low whiteness index and limited application to food systems due to its  inherent functional properties. Therefore,  it needs modification process  to  improve  this property. In  this study, sweet potatoes cubes were  lactic spontaneously fermented for 120 h before being processed  to flour  to modify  its properties. Selected physico-chemical properties of flour were then determined and compared with the control (without fermentation). The results showed that lactic acid fermentation significantly caused more changes on flour properties. The lactic acid fermentation caused an alteration in the starch granules as evident by Scanning Electron Microscopy. When compared to the control flour, spontaneous fermented flour had lower solubility, higher swelling power, and paste viscosity.  The results suggested lactic spontaneous fermentation within 120 h period of  time could provide a greater extent of  flour modification.